Growth and protein response of rice plant with plant growth-promoting rhizobacteria inoculations under salt stress conditions - Chompa, Sayma Serine; Zuan, Ali Tan Kee; Mohd Amin, Adibah; Hun, Tan Geok; Ahmad Ghazali, Amir Hamzah; Sadeq, Buraq Musa; Akter, Amaily; Rahman, Md Ekhlasur; Rashid, Harun Or (Springer Science and Business Media Deutschland GmbH, 2024)
Soil salinity has been one of the significant barriers to improving rice production and quality. According to reports, Bacillus spp. can be utilized to boost plant development in saline soil, although the molecular mechanisms behind the interaction of microbes towards salt stress are not fully known. Variations in rice plant protein expression in response to salt stress and plant growth-promoting rhizobacteria (PGPR) inoculations were investigated using a proteomic method and sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE). Findings revealed that 54 salt-responsive proteins were identified by mass spectrometry analysis (LC–MS/MS) with the Bacillus spp. interaction, and the proteins were functionally classified as gene ontology. The initial study showed that all proteins were labeled by mass spectrometry analysis (LC–MS/MS) with Bacillus spp. interaction; the proteins were functionally classified into six groups. Approximately 18 identified proteins (up-regulated, 13; down-regulated, 5) were involved in the photosynthetic process. An increase in the expression of eight up-regulated and two down-regulated proteins in protein synthesis known as chaperones, such as the 60 kDa chaperonin, the 70 kDa heat shock protein BIP, and calreticulin, was involved in rice plant stress tolerance. Several proteins involved in protein metabolism and signaling pathways also experienced significant changes in their expression. The results revealed that phytohormones regulated the manifestation of various chaperones and protein abundance and that protein synthesis played a significant role in regulating salt stress. This study also described how chaperones regulate rice salt stress, their different subcellular localizations, and the activity of chaperones.